Actuarial Mathematics and Risk Management - Olivieri, Annamaria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint collects ten papers (plus an introductory chapter) showing how actuarial mathematics principles and tools can provide substantial support when implementing QRM phases, in particular when facing new risks or risks with changing features. The following specific topics are specifically discussed: the design of post-retirement benefits, the design of life and health insurance policies against new risks, advancements in mortality modeling, advancements in risk measures and risk models, reserving disclosure tools, and innovative approximation formulae for the mean duration.